(untitled) (Palimpsesto, 2020)
The article deals with Las aventuras de la China Iron (2017), a novel by Gabriela Cabezón Cámara in which both the gaucho genre and the criticism that codified and canonized it are questioned. Although the book postulates a tribute to the work of Josefina Ludmer El género gauchesco. Un tratado sobre la patria (1988), also stops in other times when Argentine literature (and even Uruguayan, which recognizes the River Plate’s character of the gaucho) faces the whole. The very notion of gender is redefined and, consequently, destabilized, while combining it with other views on the historical character of the gaucho, in which dominates Sarmiento’s, homologated to Hernández in his common role as custodians of the tradition, and that of Borges.